Effects of erdosteine on alpha amanitin-induced hepatotoxicity in mice. (2nd January 2016) - Kaya, Ertugrul; Yilmaz, Ismail; Admis, Ozlem; Oktay, Murat; Bayram, Recep; Bakirci, Sinan; Yaykasli, Kursat Oguz; Kandis, Hayati; Saritas, Ayhan; Katirci, Yavuz; Colakoglu, Serdar
Abstract: The aim of this study was to investigate beneficial effects of erdosteine in the alpha amanitine-induced hepatotoxicity in mice. Three hours after giving alpha amanitin (0.5 mg/kg, i.p.) to the mice, they were administered silibinin (50 mg/kg/d, i.p.) or erdosteine (100 mg/kg/d, oral) therapies once a day for 3 d. A histopathological examination of their liver tissues was carried out 24 h after the last treatment; transaminase levels, blood urea nitrogen, urea, and creatinine were analyzed in serum. Erdosteine showed a beneficial effect by significantly improving the functional parameters particularly in alpha amanitin-induced hepatotoxicity and partially in renal toxicity. In the histopathological evaluation, the toxicity that was generated with alpha amanitin was significantly reduced by erdosteine, showing a possible hepatoprotective effect.